Phosphorus management with special reference to forage legumes in sub-Saharan Africa - Haque, I.; Nnadi, L.A.; Mohamed-Saleem, M.A. (International Livestock Centre for Africa, 1986)
Summarises available information on the P status of soils, effect of P application on nodulation, dry-matter and seed production, crude-protein and dry-matter digestibility; use of slow release sources of P; differences among species and varieties in their response to P ; assessment of P status of forage legumes; P fertilization based on cropping systems and P nutrition of plants vs animals.